Factors Associated with Longer Length of Stay in Recurrent Cellulitis on Lower Legs - Brishkoska-Boshkovski, Vesna; Vasileva, Mirela; Baloski, Marjan (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Cellulitis is a common infectious disease with typical feature – the tendency for recurrence. AIM: The aim of the study was to define comorbidities, clinical, and laboratory – biochemical factors associated with longer length of stay (LOS) in patients with recurrent cellulitis in the lower legs. MATERIALS AND METHODS: The study is a retrospective-cohort study conducted at the Department of Dermatovenerology at General Hospital in Skopje, from January 2016 to August 2019. In the study, we included and analyzed only hospitalized patients admitted for recurrent cellulitis on the lower legs. Inclusion in the study recorded the following variables – comorbid conditions in the patients – present in the medical records or obtained from the interview of the patient and initial values of laboratory assays on admission. RESULTS: The study included hospitalized 205 patients, admitted for recurrent cellulitis. The most significant comorbid conditions and laboratory parameters which correlate with increased LOS are as follows: Type 2 diabetes mellitus – insulin dependent (p < 0.001), chronic renal failure (p = 0.003), ischemic heart disease (p = 0.006), peripheral arterial disease (p = 0.007), fever ≥38.0°C (p < 0.001), hypoalbuminemia ˂34 g/L (p < 0.001), elevated value of C-reactive protein >10 mg/L (p < 0.001), and leukocytosis >109 L (p = 0.009). CONCLUSION: Cellulitis is potential medical emergency event. Recurrence is the most significant complication of cellulitis and lower legs cellulitis is associated with a risk for long-term morbidity. The study has identified several independent factors that are significantly associated with an increased LOS. This independent factors present on admission can stratify the patient with the highest risk of mortality, can improve patient care for better outcomes, and decrease the number of relapses and hospital readmissions.